Respons Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pre Nursery terhadap Pemberian Limbah Cair Pabrik Kelapa Sawit dan Pupuk NPKMg (15:15:6:4) - I Gede Andri Wijaya; Jonatan Ginting; Haryati Haryati (Jurnal Agroekoteknologi, 2015)
Palm oil is one of the major and prime agricultural commodities in Indonesia. Better palm oilseedling growth depend on nutrient and organic matter availability that can be fullfilled by usingpalm oil mill effluent (POME) and NPKMg (15:15:6:4) fertilizer. The objectives of the researchwere to study growth response of palm oil pre nursery seedling to aplication of POME and NPKMg(15:15:6:4) fertilizer.  The research was held at  screen house of Agricultural Faculty USU            (±25 m asl) in April to July 2014 using a factorial randomized block design with two factors and threereplications. The first factor were POME (0; 1.5; 3.0; 4.5 l/seedling) and the second factor wereNPKMg (15: 15: 6: 4) fertilizer (0; 2.5; 5.0; 7.5 g/seedling). Data were analyzed with ANOVA andcontinued with Duncan multiple range test. The Parameters observed were plant height,      stemdiameter, leaves number, total leaf area, leaves greenness, fresh and dry root and upper part weight.The results obtain were the effect of POME until dose L (3.0 l/seedling) were increase for allparameters except leaves greenness, fresh and dry root. The effect of  NPKMg (15:15:6:4)  fertilizeruntil dose P22 (5.0 g/seedling) increase for all parameters except stem diameter. The interaction ofthese two factors until L3Pwere increase leaves number, leaves greenness, fresh root weight, freshand dry upper part weight.Keywords:  palm oil mill effluent, NPKMg (15:15:6:4) fertilizer, palm oil seedling 3